BAP31 Regulates Wnt Signaling to Modulate Cell Migration in Lung Cancer - Li, Tianye; Hao, Zhenzhen; Tang, Zihan; Li, Chunting; Cheng, Linglin; Wang, Tao; Zhu, Xiaojin; He, Yunhao; Huang, Yongye; Wang, Bing (Frontiers in Oncology, 2022)
B-cell receptor-associated protein 31 (BAP31) has been shown to overexpress in a wide range type of cancers. The present study aims to investigate the role of BAP31 on migration in lung cancer. Results showed that the migration of BAP31 knockdown cells was weaken than the control cells. Applying TGFβ to treat BAP31 knockdown cells could reduce cell migration. The enhancement on proliferation by TGFβ treatment was downregulated after BAP31 knockdown. The cell death and G0/G1 phase arrest was increased in the cells with TGFβ and BAP31 siRNA treatment when compared with TGFβ treatment alone. Gene expression analysis showed that Bax/Bcl2, MLKL and LC3 was upregulated in the cells with combinatorial treatment of TGFβ and BAP31 siRNA. In addition, BAP31 was shown to regulate multiple signaling pathways, especially for Wnt signaling. It found that BAP31 knockdown cells treated with TGFβ decreased β-catenin cytosolic expression and nuclear localization. Wnt signaling activator BIO could restore the downregulation of proliferation by BAP31 knockdown. This finding suggested that BAP31 regulated cancer cell migration is possibly involved with cell death mechanisms and Wnt signaling.